Industrial ecology at factory level: a conceptual model - Despeisse, Melanie; Ball, Peter D.; Evans, Stephen; Levers, A. (Elsevier Science B.V., Amsterdam., 2012)
Growing environmental concerns caused by natural resource depletion and pollution need to be addressed. One approach to these problems is Sustainable Development, a key concept for our society to meet present as well as future needs worldwide. Manufacturing clearly has a major role to play in the move towards a more sustainable society. However it appears that basic principles of environmental sustainability are not systematically applied, with practice tending to focus on local improvements. The aim of the work presented in this paper is to adopt a more holistic view of the factory unit to enable opportunities for wider improvement. This research analyses environmental principles and industrial practice to develop a conceptual manufacturing ecosystem model as a foundation to improve environmental performance. The model developed focuses on material, energy and waste understand the interactions between manufacturing operations, supporting facilities and surrounding buildings. The research was conducted in three steps: (1) existing concepts and models for industrial sustainability were reviewed and environmental practices in manufacturing were collected and analysed; (2) gaps in knowledge and practice were identi model based on industrial ecology (IE). This conceptual model has novelty in detailing IE application at factory level and integrating all resource modelling tools to seek integrated solutions for lower resource input, higher resource productivity, fewer wastes and emissions, and lower operating cost within the boundary of a factory unit.flows to betterfied; (3) the outcome is a manufacturing ecosystemflows. The work is a base on which to build quantitative 2012 Elsevier Ltd. All rights
Keywords: Industrial ecology; sustainable manufacturing; resource flow modelling; sustainability